Chromosomal Location and Identification of TBX20 as a New Gene Responsible for Familial Bicuspid Aortic Valve - Yan-Jie Li; Su Zou; Yi-Zhe Bian; Xing-Yuan Liu; Chen-Xi Yang; Li Li; Xing-Biao Qiu; Ying-Jia Xu; Yi-Qing Yang; Ri-Tai Huang (Diagnostics)
Background/Objectives: Congenital bicuspid aortic valve (BAV) signifies the most frequent category of congenital cardiovascular anomaly globally, occurring in approximately 0.5–2% of the general population worldwide. BAV is a major cause of thoracic aortopathy, encompassing aortic stenosis, aortic root dilation with regurgitation, aortic dissection, and aortic aneurysms, consequently leading to substantial late-onset morbidity and mortality. Accumulating evidence convincingly demonstrates the strong genetic basis underpinning BAV, though the inheritable reasons responsible for BAV in most patients remain largely obscure. Methods: A genome-wide genotyping with 400 polymorphic genetic markers followed by linkage analysis, haplotype assay, and sequencing analysis of candidate genes was conducted in a 4-generation BAV kindred of 47 individuals. Biochemical assays were performed to evaluate the functional effect of the identified mutation on TBX20. Results: A novel BAV-causative locus was mapped to chromosome 7p14. A sequencing assay of the genes within the mapped chromosomal region (locus) unveiled that only the c.656T>G (p.Ile219Arg) variation of TBX20 was in co-segregation with BAV in the entire pedigree. The missense mutation was not uncovered in 322 healthy persons employed as control individuals. Functional deciphers revealed that the mutation significantly decreased the transcriptional activation of the representative target gene ANP and the binding ability to the ANP promoter and impaired the intranuclear distribution of TBX20. Conclusions: This investigation maps a new genetic locus (chromosome 7p14) linked to BAV and uncovers TBX20 as a novel causative gene for familial BAV, adding more insight into the mechanisms underlying BAV and providing a molecular target for the individualized management of BAV.